Bourbon-era Chile: Tomás Álvarez de Acevedo’s Visita and local entanglements. - Infante Martin, Javier Francisco Jesús (Revista de Estudios Histórico-Jurídicos, 2019)
This article seeks to show the social context within which Tomás Álvarez de Acevedo’s visita was carried out, the strong ties between local magistrates and their subsequent resistance to any kind of reform that threatened to alter their position as local authorities as well as their economic and social status, and the obstacles the Visitador Regente faced in completing his task while, at the same time, adapting many of the new policies to the local circumstances, thereby achieving his commitment to the Spanish Crown.